Bearing capacity of the bucket spudcan foundation for offshore jack-up drilling platforms - Puyang Zhang; Hongyan Ding (Petroleum Exploration and Development, 2011)
To compare the bearing capacities of the traditional spudcan and the bucket spudcan, the effects of different type spudcans on the rigidity of pile legs and the entire bearing capacity were analyzed in detail. Through the loading method of Swipe and constant displacement, this paper plots the spatial failure envelopes of the vertical-horizontal load, vertical-moment load, vertical-horizontal-moment load of the bucket spudcan and traditional spudcan under the mode of composite loading, as well as the spatial failure envelopes of the vertical static load-vertical cycling limit load, vertical static-load horizontal cycling limit load based on these two spudcans under the mode of cycling loading. Theoretical study showed that the skirt system of bucket spudcan can increase the effective embedded depth, consequently improving the foundation rigidity and entire stiffness of a jack-up drilling platform. It is found that the bearing capacity of the horizontal load and moment load of the new spudcan is increased by at least 10% than that of the traditional spudcan, especially the horizontal load being up to 20% in the dynamic load condition. Under the action of limit storm loading condition including wind, wave and flow loads, the entire bearing capacity of the jackup rig in stiff clay is increased by about 46% with the bucket spudcan foundation compared to the traditional one. Key words: bucket spudcan foundation, offshore jackup rig, bearing capacity, numerical simulation, failure envelopes